HIV Testing and Care in Canadian Aboriginal Youth: A community based mixed methods study - Myers Ted; Wong Tom; Archibald Chris P; Worthington Catherine A; Jackson Randy C; Mill Judy E; Prentice Tracey; Sommerfeldt Susan (BMC Infectious Diseases, 2008)
Abstract Background HIV infection is a serious concern in the Canadian Aboriginal population, particularly among youth; however, there is limited attention to this issue in research literature. The purpose of this national study was to explore HIV testing and care decisions of Canadian Aboriginal youth. Methods A community-based mixed-method design incorporating the Aboriginal research principles of Ownership, Control, Access and Possession (OCAP) was used. Data were collected through surveys (n = 413) and qualitative interviews (n = 28). Eleven community-based organizations including urban Aboriginal AIDS service organizations and health and friendship centres in seven provinces and one territory assisted with the recruitment of youth (15 to 30 years). Results Average age of survey participants was 21.5 years (median = 21.0 years) and qualitative interview participants was 24.4 years (median = 24.0). Fifty-one percent of the survey respondents (210 of 413 youth) and 25 of 28 interview participants had been tested for HIV. The most common reason to seek testing was having sex without a condom (43.6%) or pregnancy (35.4%) while common reasons for not testing were the perception of being low HIV risk (45.3%) or not having had sex with an infected person (34.5%). Among interviewees, a contributing reason for not testing was feeling invulnerable. Most surveyed youth tested in the community in which they lived (86.5%) and 34.1% visited a physician for the test. The majority of surveyed youth (60.0%) had tested once or twice in the previous 2 years, however, about one-quarter had tested more than twice. Among the 26 surveyed youth who reported that they were HIV-positive, 6 (23.1%) had AIDS at the time of diagnosis. Delays in care-seeking after diagnosis varied from a few months to seven years from time of test. Conclusion It is encouraging that many youth who had tested for HIV did so based on a realistic self-assessment of HIV risk behaviours; however, for others, a feeling of invulnerability was a barrier to testing. For those who tested positive, there was often a delay in accessing health services.